2013
DOI: 10.1002/glia.22483
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for miR‐181 involvement in neuroinflammatory responses of astrocytes

Abstract: Inflammation is a common component of acute injuries of the central nervous system (CNS) and degenerative disorders such as Alzheimer’s disease. Glial cells play important roles in local CNS inflammation, and an understanding of the roles for microRNAs in glial reactivity in injury and disease settings may therefore enable novel therapeutic interventions. Here we show that the miR-181 family is developmentally regulated and present in high amounts in astrocytes compared to neurons. Over-expression of miR-181c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
185
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(198 citation statements)
references
References 62 publications
(85 reference statements)
10
185
0
1
Order By: Relevance
“…These instructive signals can derive from many different sources (Fig. 1A) (Bhalala et al 2012;Hutchison et al 2013), and miR regulatory enzymes, such as Dicer (Tao et al 2011), can modulate astrogliosis and reactive astrocyte functions, adding yet another level of potential regulation and specification of functions (Table 1). Thus, intrinsic properties of individual astrocytes, such as epigenetic mechanisms or genetic polymorphisms of receptors and second messengers and other regulators, may impact astrogliosis.…”
Section: Extracellular Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These instructive signals can derive from many different sources (Fig. 1A) (Bhalala et al 2012;Hutchison et al 2013), and miR regulatory enzymes, such as Dicer (Tao et al 2011), can modulate astrogliosis and reactive astrocyte functions, adding yet another level of potential regulation and specification of functions (Table 1). Thus, intrinsic properties of individual astrocytes, such as epigenetic mechanisms or genetic polymorphisms of receptors and second messengers and other regulators, may impact astrogliosis.…”
Section: Extracellular Signalsmentioning
confidence: 99%
“…Deletion of YLK-40/BRP-39, an astrocyte produced anti-inflammatory protein, exacerbates autoimmune disease in mice (Bonneh-Barkay et al 2012). miR-181 decreases astrocyte production of inflammatory cytokines (TNF-a, IL-1b) and increases production of anti-inflammatory cytokines (IL-10) (Hutchison et al 2013). Thus, different signaling mechanisms regulate different aspects of pro-or anti-inflammatory functions of reactive astrocytes.…”
Section: Selective Regulation Of Specific Functions and Effects Of Asmentioning
confidence: 99%
“…Dan et al suggested that miR-181 upregulation is the primary host protective method against endotoxin shock, as it can switch the immune status from hyperinflammation to endotoxin tolerance by quickly decreasing inflammatory cytokine expression without influencing the expression of anti-inflammatory cytokines (Dan et al, 2014). In an experimental neuroinflammatory model, miR-181 was found to be necessary for the reactive phenotype of astrocytes to inflammatory settings by reprogramming the transcriptional profiles of general cell differentiation and stress responses (Hutchison et al, 2013). These results clearly illustrate that miR-181 plays a central role in anabolic metabolism in immune cells and fine-tunes their immunological functions to prevent overwhelming inflammation during tissue regeneration.…”
Section: Mir-181mentioning
confidence: 99%
“…The HPA axis abnormalities are involved in depression [49]. Patients with hypocortisolism tend to present more distress symptoms, maladaptive coping styles, and schizotypal personality traits [50]. TBI patients induce HPA axis dysfunction in the acute phase of severe TBI patients.…”
Section: Discussionmentioning
confidence: 99%